CounterTexting One Another: Conceptual Poetics, Flarf, and Derridean Countersignature. Issue 2 (August 2015) - Milesi, Laurent
<x content-type="archive" xml:space="preserve">Abstract</x> Using the precedent of Charles Bernstein's spoof on Charles Olson's 'Projective Verse' poetics manifesto as part of a long contextual introduction on issues of literary filiation, influence, and intertextuality, this essay analyses the recent exchanges between conceptualist poetry (Vanessa Place, Kenneth Goldsmith's 'uncreative writing') and 'flarf' (Drew Gardner) in the light of Derrida's twin notions of signature and countersignature. In the process it ties together reading and writing(-as-rereading) in response and co-responsibility in order to theorise the critical notion of 'countertextuality' as a more contemporary inflection of the mechanics of literary interaction known as intertextuality, better suited to characterise the textual interaction between current poetic movements. The critical apparatus and developments in the footnotes are also conceived as a creative enactment of the countertext, whose final instance (the epilogue, or 'Necrologue') is a parodic rewriting performatively exposing the creative impasse and derivativeness of several recent textual productions mimicking Sol LeWitt's 'Sentences on Conceptual Art'. As it moves towards its final critical part, the essay also puts forward, while enacting them, more general views about the relative sterility of some aspects of contemporary poetic debates while gesturing for a possible way out, via Felix Bernstein's 'Notes on Post-conceptual Poetry', in order to reclaim 'the genuinely imaginary-affective-intellectual fabric and texture of the poetical'.